Hubungan Efikasi Diri, Kualitas Tidur, dan Dukungan Sosial dengan Tingkat Stres Pada Mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar Angkatan 2024 - Thalia Atifah; Lalu Yogi Imam Prasetio; Deny Sutrisna Wiatma; Irwan Syuhada (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Academic stress is a common problem experienced by medical students due to high and complex academic demands. Internal and external factors such as self-efficacy, sleep quality, and social support are thought to play a role in influencing students' stress levels. However, previous studies have shown inconsistent findings. The purpose of this study was to determine the relationship between self-efficacy, sleep quality, and social support with stress levels in students of the Faculty of Medicine, Al-Azhar Islamic University, class of 2024. This study was a quantitative study with an observational analytical design using a cross-sectional approach. The sample was students of the Faculty of Medicine, Al-Azhar Islamic University, class of 2024, selected using the Simple Random Sampling technique. The instruments used included the General Self-Efficacy Scale (GSES), Pittsburgh Sleep Quality Index (PSQI), Multidimensional Scale of Perceived Social Support (MSPSS), and Perceived Stress Scale-10 (PSS-10). Data analysis used a correlation test with Spearman's rank test to assess the relationship between the dependent and independent variables with a p-value 0.05. Bivariate analysis showed a significant relationship between self-efficacy, sleep quality, and social support with stress levels. There was a significant relationship between self-efficacy, sleep quality, and social support with stress levels in students of the Faculty of Medicine, Al-Azhar Islamic University, class of 2024. Interventions focused on improving self-efficacy, improving sleep quality, and strengthening social support should be considered as an effort to reduce student academic stress. Keywords: Self-Efficacy, Sleep Quality, Social Support, Stress.  ABSTRAK Stres akademik merupakan permasalahan yang sering dialami mahasiswa kedokteran akibat tuntutan akademik yang tinggi dan kompleks. Faktor internal dan eksternal seperti efikasi diri, kualitas tidur, dan dukungan sosial diduga berperan dalam memengaruhi tingkat stres mahasiswa. Namun, hasil penelitian sebelumnya masih menunjukkan temuan yang tidak konsisten. Tujuan penelitian untuk mengetahui hubungan antara efikasi diri, kualitas tidur, dan dukungan sosial dengan tingkat stres pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar angkatan 2024. Penelitian ini merupakan penelitian kuantitatif dengan desain analitik observasional menggunakan pendekatan cross-sectional. Sampel penelitian adalah mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar angkatan 2024 yang dipilih menggunakan teknik Simple Random Sampling. Instrumen yang digunakan meliputi General Self-Efficacy Scale (GSES), Pittsburgh Sleep Quality Index (PSQI), Multidimensional Scale of Perceived Social Support (MSPSS), serta Perceived Stress Scale-10 (PSS-10). Analisis data menggunakan uji korelasi yang digunakan uji Spearman Rank untuk menilai hubungan antara variabel dependen dengan independen dengan p-value 0,05. Analisis bivariat menunjukkan adanya hubungan signifikan antara efikasi diri, kualitas tidur, dan dukungan sosial dengan tingkat stres. Terdapat hubungan signifikan antara efikasi diri, kualitas tidur, dan dukungan sosial dengan tingkat stres pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar angkatan 2024. Intervensi yang berfokus pada peningkatan efikasi diri, perbaikan kualitas tidur, serta penguatan dukungan sosial perlu dipertimbangkan sebagai upaya menurunkan stres akademik mahasiswa. Kata Kunci: Efikasi Diri, Kualitas Tidur, Dukungan Sosial, Stres.